Effect of toroidal magnetic field ripple value on the l=1, m=1 Yamator magnetic surfaces - Kotenko, V.G.; Lesnyakov, G.G.; Romanov, S.S. (Вопросы атомной науки и техники, 2019)
To form a ripple toroidal magnetic field, the calculated l=1, m=1 Yamator model is equipped with N=16 toroidal magnetic field coils of ac radius. In order to study the effect of toroidal magnetic field ripple value δ on the magnetic surface parameters the calculation was performed for different values of radius ac. In the paper the range of ac radius values is identified within the scope of which the magnetic surface parameters are close to that of the l=1, m=1 Yamator with ideal axially symmetric toroidal magnetic field (δ=0).